Evaluation of the functional properties of mung bean protein isolate for development of textured vegetable protein - Brishti, Fatema Hossain; Zarei, Mohammad; Syed Muhammad, Sharifah Kharidah; Mohammad Rashedi, Ismail Fitry; Shukri, Radhiah; Saari, Nazamid (Faculty of Food Science and Technology, Universiti Putra Malaysia, 2017)
Mung bean is considered a ‘green pearl’ for its relatively high protein content; however, it has limited application as a raw material for industrial food products. As the potential use of mung beans relies on its protein behavior, this study characterized the functional properties of mung bean protein isolates and the results were compared with soy protein isolates. The protein isolates were prepared from mung bean and soy bean flours via extraction with 1 N NaOH, precipitated at pH 4, and subsequently freeze-dried. The amino acid profile as well as the hydrophilic and hydrophobic ratio of mung bean protein isolate, had been comparable with soy protein isolate. The water and oil absorption capacities as well as the denaturation temperature of mung bean protein isolate, were found to be similar with those of soy bean protein isolate. However, foaming capacity (89.66%) of mung bean protein isolate was higher than that of soy protein isolate (68.66%). Besides, least gelation concentration (LGC) of mung bean protein isolate (12%) was also close to LGC of soy protein isolate (14%), while the protein solubility was comparable between both the isolated proteins. The physical features of the textured mung bean were close to the commercial textured soy protein, which showed a heterogeneous and porous network like matrix when the mung bean flour was extruded to measure its potentiality to produce textured vegetable protein all seaweed extracts. Results showed that extraction parameters had significant effect (p < 0.05) on the antioxidant compounds and antioxidant capacities of seaweed. Sargassum polycystum portrayed the most antioxidant compounds (37.41 ± 0.01 mg GAE/g DW and 4.54 ± 0.02 mg CE/g DW) and capacities (2.00 ± 0.01 μmol TEAC/g DW and 0.84 ± 0.01 μmol TEAC/g DW) amongst four species of seaweed.